Studi Fenomenologis Pengalaman Mahasiswa PBA UNM Semester 3 dalam Menghadapi Kesulitan Pembelajaran Nahwu di Era Digital - Irfan (CV. SINAR HOWUHOWU, 2025)
This study aims to explore the experiences of third-semester students of the Arabic Education Study Program (PBA) at Universitas Negeri Makassar (UNM) in facing difficulties in learning Arabic grammar (nahwu) in the digital era. Using an interpretative phenomenological approach, this study involved eight purposively selected participants. Data were collected through semi-structured in-depth interviews and analyzed using Colaizzi’s method. The results show that students face various challenges, including: (1) conceptual difficulties in understanding basic nahwu topics such as amil, i’rab, and mabni-mu‘rab, (2) analytical difficulties in analyzing long sentences or Arabic texts, and (3) practical difficulties related to reliance on digital media. Despite these challenges, digital media play a crucial role in supporting nahwu learning, though they also present challenges due to unstructured information and digital distractions. Students developed various adaptive strategies, such as using digital applications, re-writing notes in visual schema formats, and engaging in collaborative learning within groups. The experience of learning nahwu is not only a process of mastering content but also a process of shaping students' academic and professional identity as prospective Arabic language teachers. The implications of this study emphasize the need for a more interactive and multimodal approach to nahwu instruction, integrating technology and traditional methods in balance to enhance students' understanding of complex content.